LENGTHENING OR RESTORE WITH WELDED THE RAIL LASHES WITH THE INTRODUCTION OF THE DESIRED FUSING TEMPERATURE USING TENSIONERS - Novakovych, M. V.; Karpachevskyi, H. V.; Kurylina, I. O.; Potlov, O. V. (Science and Transport Progress, 2003)
The technology of restoration or lengthening welded rail without joints is described in the article at low temperatures with input in optimum temperature of fastening with application of hydraulic tension devices.